Pendidikan Agama Kristen Sebagai Agen Restorasi Pendidikan Dalam Mewujudkan Kehidupan Beragama Yang Harmonis Di Sekolah–Sekolah - Kristianus Bayu Pranata; Nehemia Nome (Jurnal Filsafat dan Teologi Katolik, 2023)
Abstract: Christian religious education has the goal of teaching students the principles of Christian life, including moral values such as love, forgiveness, justice, and brotherhood. Christian religious education can help students understand and appreciate other religions with an inclusive attitude, tolerance, and respect for religious differences. However, there are several challenges that need to be overcome in implementing Christian religious education as an educational restoration agent to create a harmonious religious life in schools. One of the main challenges is the lack of understanding of religious moderation. In this research, the writer took the step of doing a literature study. Christian religious education plays a vital role as an educational restoration agent in creating a harmonious religious life in schools. Through teaching moral values, respect for religious diversity, character building, and interreligious dialogue, Christian religious education contributes to shaping students who live according to religious values and in harmony with fellow human beings.